ASME 2009 Dynamic Systems and Control Conference, Volume 1 2009
DOI: 10.1115/dscc2009-2780
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Power Management Strategy for Hydraulic Hybrid Output Coupled Power-Split Transmission

Abstract: Power-split drive represents a class of Continuously Variable Transmission (CVT) that combines the convenience of CVT with the high overall transmission efficiency. In its hybrid configuration, a high pressure accumulator is used to capture the braking energy that is regenerated to aid the engine power during the next propulsion event. Output coupled power split drives are particularly suited for small and medium duty vehicle applications. In this work, optimal power management strategy has been designed based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The look forward simulation method [5][6][7][8][9] is applied. The system simulation modeling diagram is shown as Figure 9.…”
Section: A System Modeling Conceptmentioning
confidence: 99%
“…The look forward simulation method [5][6][7][8][9] is applied. The system simulation modeling diagram is shown as Figure 9.…”
Section: A System Modeling Conceptmentioning
confidence: 99%
“…Filipi et al (2004) and Wu et al (2004) proposed tripoptimal strategies solved via DP to a parallel hydraulic hybrid truck. Kumar and Ivantysynova (2009) presented results from applications of DP for a power-split hydraulic hybrid vehicle. There has not been any reported work to date that details the formulation and application of instantaneous optimisation to any configuration of hydraulic hybrid drives.…”
Section: Introductionmentioning
confidence: 99%
“…However, extensive trial and error is required to achieve the optimal system-level performance beyond individual component (e.g., ICE) efficiency. The second category of strategies explicitly considers system-level optimisation over a specified time horizon or trip length for the dynamic allocation of the split of demanded power between the on-board sources in a manner that minimises the total fuel use (Daowei and Hui, 2008;Kumar and Ivantysynova, 2009;Lin et al, 2003a;Liu and Peng, 2006;Wu et al, 2004). Solving the optimisation problems involve computational intensive DP algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research topics for power-split HHVs include different areas, such as dynamic analysis and controllers for passenger vehicles [21][22][23][24][25], experimental studies on hardware in the loop tests [26][27][28], concept car demonstrations, such as Hybrid Air by Peugeot [29], and system optimizations and optimal architecture studies for specific applications [10]. A recent study investigated the optimization system of a power-split HHV and reported energy savings up to 35% in comparison to a power-split hydrostatic transmission (HST) without considering engine management [30].…”
Section: Introductionmentioning
confidence: 99%